Evaluation of Long-Term Sexual Satisfaction in Women Submitted to Laparoscopic Sacrocolpopexy: Retrospective Tertiary Center Study - Da Silva Medeiros, Mariana (2024)
Introduction: Traditional treatments for apical compartment prolapse and multicompartment prolapse, such as open sacrocolpopexy, have been associated with concerns regarding sexual function. In recent years, laparoscopic or robotically assisted sacrocolpopexy has emerged as an alternative with potential benefits, including enhanced visualization, symptom relief, and comparable anatomical results. However, the impact of laparoscopic sacrocolpopexy (LSP) on long-term sexual satisfaction in women remains an important area of investigation. This retrospective tertiary center study aimed to evaluate the long-term sexual satisfaction in women who underwent LSP for the treatment of POP. The objective was to assess postoperative sexual satisfaction among patients with a history of active sexual life before the surgery. Methods: A total of 30 patients who underwent laparoscopic sacrocolpopexy between August 2014 and December 2016 were included in the analysis. The patients’ sexual satisfaction was assessed using The New Sexual Satisfaction Scale, a validated questionnaire in the Portuguese language with a mean follow-up of 7 years. Baseline characteristics, surgical and function outcomes were also evaluated. Results: Among the participants, 70% remained sexually active after the surgery. The mean score on The New Sexual Satisfaction Scale was 75.1, indicating a moderate to very satisfied level of sexual satisfaction. Out of the patients who reported a change in their sexual satisfaction after surgery, 69.2% would still recommend the procedure to others. The mean rate of global satisfaction with the surgery was 6.97 out of 10, with 83.3% of the patients recommending the surgery to someone else. Conclusion: The study provides valuable insights into the impact of laparoscopic sacrocolpopexy on sexual well-being in women with POP. Despite potential changes in sexual function, the majority of patients remained sexually active and perceived the procedure as beneficial, expressing overall satisfaction and recommending it to others. The findings highlight the importance of considering sexual function in the management of POP and suggest that LSP can be an effective treatment option that preserves sexual activity. However, further studies with larger sample sizes and comprehensive assessments are warranted to better understand the complex relationship between pelvic organ prolapse surgery, sexual function, and patient outcomes.